Dreams and Dead Ends : the American Gangster Film. - Shadoian, Jack (Oxford University Press, 2003)
This work provides a history of the 20th-century American gangster film. Moving chronologically through nearly seven decades, this volume offers illuminating readings of a select group of the classic films that best define and exemplify each period in the development of the American crime film.